2015
DOI: 10.15275/rusomj.2015.0102
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of genes associated with increased cardiovascular risk and cognitive function in patients with chronic heart failure and in healthy persons: the pilot study

Abstract: Abstract:There was studied the relationship between polymorphic variants of APOC3 (rs2854117), PON1 (rs854560, rs662), AGT (rs4762, rs699) and AGTR1 (rs5186) genes with the results of cognitive tests in patients with chronic heart failure (СHF) of ischemic genesis and healthy persons. The general group included 50 patients with CHF of II-IV functional classes, the control group -50 healthy volunteers. Cognitive functions were estimated by 5 th and 7 th subtests of Wexler and Burdon's test. There was revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Results of the present study indicated that TT genotypes performed more poorly on measures of attention/processing speed and language, but not executive function. While the lack of genetic effect on executive function may be a result of low power, it is plausible that vascular risk associated with the 268T allele disrupts basic-level cognitive processes (e.g., attention/processing speed, language) prior to disturbances in executive networks [79]. This remains conjecture at this point and longitudinal studies are needed to assess the chronology of vascular-related cognitive changes in aging populations.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Results of the present study indicated that TT genotypes performed more poorly on measures of attention/processing speed and language, but not executive function. While the lack of genetic effect on executive function may be a result of low power, it is plausible that vascular risk associated with the 268T allele disrupts basic-level cognitive processes (e.g., attention/processing speed, language) prior to disturbances in executive networks [79]. This remains conjecture at this point and longitudinal studies are needed to assess the chronology of vascular-related cognitive changes in aging populations.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Standard models of organizing care for patients with CHF are also being developed [6], methods of evaluating its quality and efficacy are being perfected [7] and CHF registries are created [8][9][10][11][12][13][14]. Researchers turn their attention to different aspects of CHF: from influence of low-intensity electromagnetic fields on endothelium function [15] and genetic determinants of CHF [16] to vegetative [17] and cognitive dysfunction [18].…”
Section: Introductionmentioning
confidence: 99%